Effect of Spirulina (Sprirulina platensis) on Internal Quality of Eggs in Laying Hens - Heli Tistiana; Josep Roy Saputra (UNIVERSITAS ISLAM LAMONGAN, 2025)
The research aims to determine the effect of adding Spirulina (Spirulina platensis) on egg yolk index, albumin index, egg yolk colour score, and haugh unit. The research were used 150 laying hens aged 89 weeks strain Hyline Brown were used in this study reared in 5 treatment, such as (P0) using 0% of Spirulina platensis, (T1) using 0,25% Spirulina platensis, (T2) using 0,50% Spirulina platensis, (T3) using 0,75% Spirulina platensis, and (T4) using 1,00% Spirulina platensis. In this study, Completely Randomized Design (CDR) were used for research method with five level of treatments and five replications. Each replicant used six laying hens. The observed variables were egg yolk index, albumin index, egg yolk colour score, and haugh unit value. If there were significantly different results, it will be continued with Duncan’s Multiple Range Test (DMRT). The final result showed that Spirulina (Spirulina platensis) addition to layers feed didn’t gave a significant effect (P>0.05) on egg yolk index, albumen index, and haugh unit value, but had a highly significant effect (P<0.01) on egg yolk colour score. The results of DMRT showed that the egg yolk colour at T4 replication was significantly higher than T0, T1, T2, and T3. The results of this study concluded that Spirulina (Spirulina platensis) with 1% level, can be applied to layers feed without having any negative effect on other internal egg quality.